Scientific impact of studies published in temporarily available radiation oncology journals: a citation analysis - Nieder, Carsten (Springerplus, 2015)
The purpose of this study was to review all articles published in two temporarily available radiation oncology journals (Radiation Oncology Investigations, Journal of Radiosurgery) in order to evaluate their scientific impact. From several potential measures of impact and relevance of research, we selected article citation rate because landmark or practice-changing research is likely to be cited frequently. The citation database Scopus was used to analyse number of citations. During the time period 1996-1999 the journal Radiation Oncology Investigations published 205 articles, which achieved a median number of 6 citations (range 0-116). However, the most frequently cited article in the first 4 volumes achieved only 23 citations. The Journal of Radiosurgery published only 31 articles, all in the year 1999, which achieved a median number of 1 citation (range 0-11). No prospective randomized studies or phase I-II collaborative group trials were published in these journals. Apparently, the Journal of Radiosurgery acquired relatively few manuscripts that were interesting and important enough to impact clinical practice. Radiation Oncology Investigations’ citation pattern was better and closer related to that reported in several previous studies focusing on the field of radiation oncology. The vast majority of articles published in temporarily available radiation oncology journals had limited clinical impact and achieved few citations. Highly influential research was unlikely to be submitted during the initial phase of establishing new radiation oncology journals.